Metabolic syndrome affects narrow-band UVB phototherapy response in patients with psoriasis. Issue 50 (December 2017) - Rui, Wang; Xiangyu, Ding; Fang, Xie; Long, Gong; Yi, Yang; Wenjuan, Wang; Tian, Hao; Xiaoning, Zhang; Yong, Zhou; Jianfeng, Fan; Hengjin, Li; Chengxin, Li
Abstract : Abstract: Psoriasis is a chronic inflammatory skin disease. Metabolic syndrome (MS) is a combination of central obesity, dyslipidemia, glucose intolerance, and elevated blood pressure. Many epidemiological surveys have revealed the association of psoriasis with MS. Narrowband ultraviolet radiation b (NB-UVB) is an effective and widely used treatment for psoriasis. The purpose of this study was to investigate whether the presence of MS in patient with psoriasis affects NB-UVB treatment and whether this syndrome correlates with systemic inflammation. From June 2016 to December 2016, 243 adults with a diagnosis of psoriasis vulgaris eligible to treatment with NB-UVB were admitted to the phototherapy unit of Dermatology department, Chinese PLA General Hospital. Fifty-five included patients were grouped based on the presence of MS. They accepted the treatment of NB-UVB and the following data were collected: serum levels of IL-17 (interleukin), TNF-α (tumor necrosis factor) and IL-6, Psoriasis Area and Severity Index (PASI) scores before and after 10 sections of NB-UVB treatment. Significant PASI improvement was observed in psoriatic patients without MS after 10 sections of phototherapy, while patients with MS showed a less improvement ( P < .001). There was statistically significant difference in percentage of patients achieving 50% reduction in PASI scores between the 2 groups ( P < .05). Multivariate logistic regression analysis showed MS was an independent factor that affecting the treatment of NB-UVB ( P < .05). Psoriatic patients with MS showed a much less reduction of IL-17 and IL-6 before and after 10 sections of NB-UVB treatment respectively than patients without MS ( P < .05). Psoriatic patients with MS have poorer improvement in comparison those without MS using NB-UVB treatment. MS was an independent factor that affecting the treatment of NB-UVB. In addition, psoriatic patients with MS showed a much less reduction of systemic biomarkers (interleukin—IL-17, TNF-α, IL-6) than patients without MS. Namely, they may need a longer course of treatment to achieve improved skin lesions.